Is There a Spatial Relation between COVID-19 Incidents and Unemployment? A Case of East Java Province, Indonesia - Amin, Choirul; Wibowo, Afif Ari; Danardono; Mayangsari, Nicken Ayu Andhika; Noermartanto, Chintania Azahra Tantri (IOP conference series. Earth and environmental science, 2024)
The COVID-19 outbreak, although primarily considered a public health crisis, has significantly impacted the labor market. On account of the restrictions imposed, many companies have been forced to cease operations or reduce their activities. In addition to transitioning to remote work, employees often encounter temporary or permanent job loss. The primary objective of this investigation is to examine the spatial configuration exhibited by COVID-19 incidents and the spatial pattern of unemployment, as well as the spatial correlation of COVID-19 with unemployment in East Java Province. In this research, the analytical approach employed involves the utilization of Moran Index analysis. The study results show that the spatial pattern of COVID-19 incidents and the spatial pattern of unemployment in East Java Province are clustered, where districts with an increased number of COVID-19 incidents surround districts with a high number of COVID-19 incidents. Similar to this is the situation with unemployment, where high-unemployment areas surround low-unemployment areas. The results of the spatial relationship between COVID-19 incidents and unemployment show a positive value, which means there is a spatial correlation among the incidence of COVID-19 and unemployment in the districts of East Java Province. The government implements policies relating to lockdowns and similar measures to mitigate the spread and transmission of COVID-19. An effective strategy would involve targeting regions nearby where districts exhibiting a high prevalence of COVID-19 incidents coincide with districts characterized by a heightened concentration of unemployed individuals. Consequently, as the number of COVID-19 incidents diminishes, a corollary reduction in unemployment rates is anticipated, attributable to the resumption of economic activities facilitated by the reopening of businesses.